SWOT Analysis of the Muhammad Sholahuddin Albimawi Education Foundation, South Tangerang City - Syamruddin Syamruddin; Jakariah Jakariah; Ahmad Yani Nasution (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
The purpose of this study is to observe and understand the internal and external conditions through the strengths, weaknesses, opportunities, and threats that exist at the Muhammad Sholahuddin Albimawi Education Foundation, South Tangerang City. This study uses a mixed method. While the data analysis techniques include SWOT Analysis, IFE Matrix Analysis, EFE Matrix Analysis, IE Matrix Analysis, SWOT Matrix, and SWOT Analysis Diagram. The results of the study show that in the IFE Matrix the strengths and weaknesses have a total score of 3.34. Then in the EFE Matrix the opportunities and threats have a total score of 3.09. Based on the IE Matrix, the company's position is in cell I (Strong) where it shows the appropriate strategy is to grow and develop (growth and build). This means that this strategy is adjusted to the strengths of the internal side of the foundation to take advantage of the right opportunities to gain benefits for the foundation. While in the SWOT Matrix using the SO, WO, ST, and WT formulas, twelve strategies are obtained. The results of the SWOT Analysis Diagram show that the company is in quadrant II, namely carrying out a product diversification strategy.